Infant and young child feeding knowledge and practices among mothers of under-5 children in Nadia district, West Bengal: a cross-sectional study - Saha, Rakhi; Pal, Jayita; Ghosh, Manoj (International Journal Of Community Medicine And Public Health, 2024)
Background: Age-appropriate infant and young child feeding (IYCF) practice (exclusive breastfeeding till 6 months and adequate diet in a child aged 6-24 months i.e. age-appropriate number of food groups in sufficient amount and age-appropriate number of meals per day) and maintenance of hygiene are of paramount importance to promote child growth and survival. Despite several guidelines, IYCF remains an unsolved issue in the background of the significantly high proportion of malnutrition as well as under-five mortalities globally as well as in India. The current study aimed to assess the knowledge and practices related to IYCF among mothers and to find out the predictors of the same in a rural area of West Bengal. Methods: A community-based cross-sectional study was conducted among 351 mothers of under-five children in Nadia district, west Bengal with the help of a pre-designed and pre-tested semi-structured schedule. Multi-stage random sampling was done. Data were entered into MS Excel and analysed in the SPSS 21.0 version. Results: The study found that the majority (49.3% and 74.5% respectively) had an average knowledge and practice score related to infant and young child feeding. Bivariate analyses revealed that the mothers having educational levels more than higher-secondary had higher odds of good IYCF knowledge; also those who had experienced "ASHA’s home visit within one month" had higher odds of good IYCF practice. Conclusions: Adequate and consistent implementation of existing government policies can bridge the gap of knowledge and thereby practice of infant and young child feeding.